Impact of AVMs on Learning: Disadvantaged Learner Perspective in Bangladesh - Islam, Shariful; Salam, Md. Abdus (CenRaPS Journal of Social Sciences, 2020)
The art of teaching-learning in education have been changing in association with digital technologies. In recent years, formal primary schools as well as nonformal primary schools have started to conduct their teaching-learning activities by using digital materials to tap with the flow of technology enrichment. The objective of this paper was examining impact of audio visual materials (AVM) on learning of nonformal primary school learners. Quasi experimental (pre & post) research design was used to conduct the study. Therefore, this study administered quantitative approach to explore the perception of students considering the impact of intervention. Purposive & convenient sampling techniques have been followed in sample selection. Two groups of students of Grade IV were the sample. Students’ achievement test was used as tool. This study recognized that AVMs had significant impact on students’ learning in the context of creating motivation, testing prior knowledge, ensuring active participation in the classroom. Finally the study recommended that professional training for teachers is required for effective pedagogy with AVMs in classroom practices in nonformal primary schools in Bangladesh.